Inter-ideological mingling: White extremist ideology entering the mainstream on Twitter. Issue 1 (2nd January 2016) - Graham, Roderick
ABSTRACT: This case study explores the convergence of white extremist political ideology with mainstream political ideology on the micro-blogging platform Twitter – a phenomenon termed "inter-ideological mingling". Exploring the spread of white extremism in the digital environment can provide insight into the growth of hate groups in the physical environment. A sample of 4800 tweets was examined through hierarchical cluster analysis and textual analysis. Several pieces of evidence were found supporting inter-ideological mingling. Cluster analysis shows that extremist terms are not isolated from terms found in mainstream political discourse. Textual analysis of individual tweets provides evidence for five strategies of inter-ideological mingling: joining, blending, piggybacking, backstaging, and narrating .